Helicobacter pylori increases proliferation of gastric epithelial cells - KELLEHER, DERMOT P (BMJ, 1996)
The direct and indirect effects of helicobacter pylori on cell kinetics of gastric epithelial cell line AGS were investigated by flow cytometric analysis of Ki-67 positive cells and by MTT assay. Flow cytometric analysis of Ki-67 positivity permits detection of cells that are in S-phase, whereas the MTT assay is a colometric measure of the number of viable cells. In the absence of added stimulants, 23.06 (4.88)% mean (SD) of AGS cells were Ki-67 positive. When cells were preincubated in the presence of H pylori, there was a significant increase in Ki-67 positivity (66.20 (7.89)%, p < 0.001). This increase was not seen in cells cultured in the presence of Campylobacter jejuni (24.63 (8.11)% or Escherichia coli (21.66 (9.78)%). Pre-incubation of AGS cells with supernatants from both H pylori and mitogen activated peripheral blood lymphocytes also increased the per cent of cells that were Ki-67 positive (72.93 (8.68) and 69.96 (12.35)%; p, 0.001) respectively. Similar results were also found in MTT assay. These data show that both H pylori directly and the immune/inflammatory response to H pylori indirectly can influence the rate of epithelial cell proliferation, suggesting this bacterium may be an initiating step in gastric carcinogenesis and an important co-carcinogenic factor in H pylori positive subjects.
PUBLISHED
Keywords: Gastroenterology; Hepatology